Kerentanan dan Adaptasi Rumah Tangga Petani terhadap Perubahan Iklim di Kabupaten Gunungkidul - Raditia Eka Kurniawan; Reynaldi Elmir Arisurya (Jurnal Agro Ekonomi, 2020)
EnglishFarmer households are considered vulnerable to climate change because they depend on uncertain natural conditions. Regional economy and majority of people in the Gunungkidul Regency rely on their livelihoods from food crops. This study aims to identify adaptation strategies of farmer households and to analyze their vulnerability due to climate change in three villages in Gunungkidul Regency. This study uses an explanatory sequential mixed method design (quantitative-qualitative). Livelihood vulnerability analysis uses quantitative analysis with the Livelihood Vulnerability Index (LVI), while adaptation analysis is carried out qualitatively using the Sustainable Livelihoods Approach (SLA). The results showed that Pucanganom Village (south zone) was the most vulnerable to climate change with a value of LVI 0.352, while Bendung Village (north zone) 0.333 and Gedangrejo Village (middle zone) 0.346. The adaptation strategies of farmer households in each village consist of: (1) agricultural intensification and extensification, i.e. by applying climate adaptation technology, five agricultural farms systems, and integrated farming systems; (2) diversification strategy by carrying out food stocks, processing agricultural products, trade and service sectors, liquidating assets, loans or debt, and remittances; and (3) migration strategy by doing non-permanent migration, i.e. looking for side jobs outside the region, becoming seasonal laborers, and also permanent migration.IndonesianRumah tangga petani dianggap rentan terhadap perubahan iklim, karena sangat bergantung pada kondisi alam yang tidak menentu. Perekonomian wilayah dan sebagian besar masyarakat di Kabupaten Gunungkidul menggantungkan sumber penghidupannya pada  sektor pertanian tanaman pangan. Tulisan ini bertujuan untuk menganalisis kerentanan dan mengidentifikasi strategi adaptasi rumah tangga petani akibat perubahan iklim di tiga desa di Kabupaten Gunungkidul. Rancangan metode yang digunakan adalah campuran sekuensial eksplanatori (kuantitatif-kualitatif). Analisis kerentanan penghidupan menggunakan analisis kuantitatif dengan penghitungan Livelihood Vulnerability Index (LVI), sedangkan untuk menganalisis adaptasi dilakukan secara kualitatif menggunakan pendekatan Sustainable Livelihood Approach (SLA). Hasil penelitian menunjukkan bahwa Desa Pucanganom (zona selatan) paling rentan terhadap perubahan iklim dengan nilai LVI 0,352 sedangkan nilai  untuk Desa Bendung (zona utara) 0,333 dan Desa Gedangrejo (zona tengah) 0,346. Strategi adaptasi rumah tangga petani pada masing-masing desa adalah (1) intensifikasi dan ekstensifikasi pertanian, yaitu dengan penerapan teknologi adaptasi iklim, panca usaha tani dan sistem pertanian terpadu, (2) diversifikasi dengan melakukan stok pangan, pengolahan hasil pertanian, sektor perdagangan dan jasa, pencairan aset, pinjaman atau utang dan kiriman uang, dan (3) migrasi dengan melakukan migrasi nonpermanen, yaitu mencari pekerjaan sampingan di luar daerah dan menjadi buruh musiman, maupun migrasi permanen dengan merantau.